ASSOCIATION BETWEEN HANDGRIP STRENGTH AND GINGIVAL RECESSION - Ferlita Shafri Djohan, Frita; Herryawan; Ullaya, Najla (Journal of Health and Dental Sciences, 2025)
Gingival recession refers to the apical displacement of the gingival margin from the cemento-enamel junction (CEJ), which can be caused by mechanical trauma such as excessive brushing force. This phenomenon can affect aesthetics, sensitivity, and overall oral health. Handgrip strength is related to tooth brushing motion. This study aims to examine the relationship between handgrip strength and gingival recession. This research used an analytical observational with a cross-sectional design. With purposive sampling, data were collected from 165 pre-elderly individuals in Cimahi City. Handgrip strength was measured by hand dynamometer, while the gingival recession was clinically assessed with visual. Data was analyzed using the Chi-Square test. The study revealed a prevalence of gingival recession at 94.5%. The analysis results indicated a significant relationship between handgrip strength and the occurrence of gingival recession (p<0.05), with moderate handgrip strength showing the highest proportion of gingival recession. Excessive brushing force contributes to gingival recession, accompanied by high-pressure motion to gingiva and time. There is a significant association between handgrip strength and gingival recession. DOI : 10.54052/jhds.v5n1.p101-112